2000
DOI: 10.1021/jf0001177
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Calpastatin from Grass Prawn Muscle (Penaeus monodon)

Abstract: Calpastatin, a specific calpain inhibitor was purified to electrophoretical homogeneity from grass prawn (Penaeus monodon) muscle by 100 degrees C heat-treatment, DEAE-Sephacel, and Q-Sepharose chromatographs. No significant change in the inhibitory activity of crude calpastatin was observed even after 20 min incubation at 100 degrees C, pH 7.0. The purified prawn calpastatin had a molecular weight (M(r)) of 80 and 88.7 kDa determined by SDS-PAGE and Sephacryl S-200 HR gel filtration, respectively. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Unfortunately, this work did not get the samples from patient, and only the urine sample was collected from an adult healthy volunteer as a biological sample to test practical application of the proposed encoding strategy. It did not show the peak of “Trypsin ID” at m / z 761.6, indicating there was no trypsin or trypsin-like protease in the sample, which was consistent with that measured with BAEE method. To obtain the calibration curve, various concentrations of trypsin were spiked in 10-fold diluted urine samples. After incubating the spiked samples in the wells of peptide 1-encoded microplate and mixing with the internal standard, the MS spectra showed obvious peaks of “Trypsin ID” and the IS-peptide 1 (Figure A), indicating that the components of urine sample did not obvoiusly affect the hydrolysis and MS analysis.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Unfortunately, this work did not get the samples from patient, and only the urine sample was collected from an adult healthy volunteer as a biological sample to test practical application of the proposed encoding strategy. It did not show the peak of “Trypsin ID” at m / z 761.6, indicating there was no trypsin or trypsin-like protease in the sample, which was consistent with that measured with BAEE method. To obtain the calibration curve, various concentrations of trypsin were spiked in 10-fold diluted urine samples. After incubating the spiked samples in the wells of peptide 1-encoded microplate and mixing with the internal standard, the MS spectra showed obvious peaks of “Trypsin ID” and the IS-peptide 1 (Figure A), indicating that the components of urine sample did not obvoiusly affect the hydrolysis and MS analysis.…”
Section: Resultssupporting
confidence: 62%
“…To assess the accuracy of the proposed method, the activities of trypsin and chymotrypsin were also detected with BAEE ( N -α-benzoyl- l -arginine-ethylester at 253 nm) and BTEE ( N -α-benzoyl- l -tyrosine-ethylester at 256 nm) methods, respectively. Briefly, the assay was carried out in 0.1 M Tris-HCl buffer (pH 8.0) containing 6 mM CaCl 2 , 10 μM substrate (BAEE or BTEE), and trypsin or chymotrypsin at different concentrations, or 10× diluted samples. The absorbance was measured at 25 °C on a UV-3600 spectrophotometer (Shimadzu, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In shellfish, proteases from digestive tracts are considered to be the main causative agents for rapid postmortem degradation and deterioration of muscle tissue . Calpain and cathepsins are two other proteolytic systems present in muscle tissue, which have been linked to postmortem protein degradation ,, . Hence, some of these potential proteases were tested in the present study to establish their potential roles in the observed proteolytic changes in red swamp crayfish.…”
Section: Resultsmentioning
confidence: 99%
“…For freshwater prawn, muscle mushiness appeared to be due to the diffusion of proteolytic and collagenolytic enzymes from the hepatopancreas into the muscle tissue , . Calpain, an intracellular neutral endogenous protease, has also been implicated in textural changes in postmortem shellfish muscle , , although the exact role of this enzyme is controversial .…”
Section: Introductionmentioning
confidence: 99%
“…), which demonstrated the specificity of the proposed method in the analysis of complex samples and indicated that interference from co‐eluted ions with quantitation results was negligible. The measurement accuracy for trypsin and chymotrypsin in the same samples was also examined by comparing the results with those obtained from BAEE and BTEE methods, which were also reliant on the substrate cleavage to assay protease activities and showed relative errors less than 5.2%. Thus, the proposed peptide‐encoding strategy could be potentially applicated in clinical diagnosis and expanded to protease activity assays in blood samples, while necessary dilution and desalting protocols might be needed to obtain sacrifatory results.…”
Section: Resultsmentioning
confidence: 99%